Implementasi Layanan Bimbingan Kelompok untuk Mengatasi Sikap Prasangka Buruk Diri Siswa di UPT SMP Negeri 27 Medan - Dea Ivanka; Andini Syafitri; Indah Putri Sari; Dika Sahputra (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
Basically, every human being has the values ​​of bad prejudice, whether it is the value of prejudice to himself or to others. According to a BK teacher named Mrs. Kristina Nababan, S.Pd. The BK teacher explained that the problems that occurred in this school were not only about learning and a student's morals. however, also with such a great attitude of prejudice that in the end, from that prejudice, a fight occurred which was brought outside of school. The fights that had been brought out of school some time ago made the role of the BK teacher very much needed. The point is to mediate or intervene in the fight. This can be done by implementing or implementing group guidance services. Furthermore, as for the objectives to be achieved from the research we conducted, namely to see the implementation of group guidance services capable of overcoming students' self-prejudiced attitudes at UPT SMP Negeri 27 Medan. This research uses descriptive qualitative research methods which are classified into literature study research. The results of the research found in this study are that there are characteristics of students who have bad prejudice, there are factors that influence it, there are efforts to serve them, there are games in the BKP service itself, and it is true that this BKp service is able to overcome the attitude of prejudice in students. student self.